RETRACTED: The influence of the blogosphere on the features of students’ life strategies - Kukulyar Anna; Kryuchkova Anna (BIO Web of Conferences, 2024)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001